Transmissão de Radiação Ultravioleta Através do Pelame e da Epiderme de Bovinos - Da Silva, Roberto Gomes [UNESP]; La Scala Jr., Newton [UNESP]; Pocay, Priscila Lombardi Bersi (My University, 2001)
A laboratory study was carried on the transmission of ultraviolet radiation (UV, 250 to 360 nm wavelength) through the haircoat and the skin of cattle. Fresh samples of skin were measured under a solar simulator, taking account of the pigmentation of hair and skin and the structural characteristics of the haircoat (coat thickness, hair diameter, hair length, angle of the hairs to the skin surface, number of hairs per unit area), which defined the average free path length of a photon within the coat, L. White hairs with high L values showed the highest transmission coefficients, while black hairs presented in general very low or even nul transmission. The best protection against UV was given by black hairs with low L values over a black skin. However, because of the heating by absorption of thermal radiation (in a Holstein cow the temperature of the black spots reach 44.1°C at the same time that of the white spots is 37.7°C), the best choice for tropical environments will be a white coat with a low L value over a black skin. This is a combination hardly found in European cattle, however in the present study a Holstein cow was found with isolated areas of white hair over black skin. An alternative choice would be a black coat with a low L value. Red animals presented high UV transmission coefficients through both the coat and the skin, and are not good choices for tropical environments, unless they have also a high pigmented skin.
Transmission of Ultraviolet Radiation Through the Haircoat and the Skin of Cattle
Keywords: Cattle; Haircoat; Radiation; Skin; Ultraviolet